Management of retraction pockets: historic and novel approaches. Issue 7 (7th July 2022) - Spinos, D; Mallick, S; Judd, O
Abstract: Background: Retraction pockets are collapsed segments of the tympanic membrane. Their formation is associated with a disruption in middle-ear ventilation pathways, leading to the loss of organised collagen of the tympanic membrane. There are several approaches in treating retraction pockets, which aim either to improve ventilation or repair the retraction pockets themselves. Methods: A review of the literature regarding the classification and associated management of retraction pockets was conducted, using Medline and Cochrane Library databases, with the addition of our institution's experience in undertaking novel techniques. Results: All the current classification systems fail to guide treatment or prognosticate the disease. Commonly, an initial conservative approach is suggested for early stages, with no clear indication regarding when a surgical solution should be offered. There are conflicting data concerning the effectiveness of these treatments in terms of disease prevention, recurrence and hearing outcomes. Conclusion: Minimally invasive approaches utilising novel techniques may be key to reducing peri-operative morbidity and improving the overall patient experience.